1998
DOI: 10.1063/1.122407
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of electron confinement in the single-domain (4×1)-In superstructure on vicinal Si(111)

Abstract: Reflectance anisotropy spectroscopy is applied to submonolayer growth of In on the vicinal silicon (111) surface. Deposition in the region of 1 monolayer onto a clean stepped Si(111) surface at elevated temperature produces a single-domain In-induced (4×1) superstructure consisting of quasi-one-dimensional chains aligned parallel to the vicinal surface step edges. A significant optical anisotropy (1.65%), uncharacteristic of semiconductor systems, develops in the region of 1.9 eV which saturates upon completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
4
26
2
Order By: Relevance
“…These results contrast with RAS studies of this system, which show a dominant anisotropic linear polarizability in the surface plane perpendicular to the chains [14], and they underline the complementary information available from linear and nonlinear surface optical probes. The results also contrast with previous studies of another candidate for quasi-one-dimensional metallicity, the single domain Si(111)±5 Â 2-Au structure [15 to 17].…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…These results contrast with RAS studies of this system, which show a dominant anisotropic linear polarizability in the surface plane perpendicular to the chains [14], and they underline the complementary information available from linear and nonlinear surface optical probes. The results also contrast with previous studies of another candidate for quasi-one-dimensional metallicity, the single domain Si(111)±5 Â 2-Au structure [15 to 17].…”
Section: Resultscontrasting
confidence: 72%
“…Recent reflection anisotropy spectroscopy (RAS) studies, however, revealed a very large anisotropy at 1.9 eV, in a direction perpendicular to the In-induced chains and step edges [14]. This was interpreted in terms of electronic confinement perpendicular to the steps.…”
Section: Resultsmentioning
confidence: 97%
“…1). The negative, broad, composite feature is very similar to features observed in other metalinduced chain-like structures: RA spectra of Si(111)-(4 × 1)-In [12,15], Si(111)-(5 × 2)-Au [16] and Si(111)-(3 × 1)-Ca [17] are shown in Fig. 2.…”
Section: Methodssupporting
confidence: 58%
“…40,41 RAS measurements of the Si͑111͒ : In-͑4 ϫ 1͒ date back to 1998 and can only be done on the vicinal Si͑111͒ surfaces that force single domain formation. 13 The RAS spectrum ͑Fig. 7͒ is dominated by a strong interband transition at 2 eV.…”
Section: Atomic Nanowiresmentioning
confidence: 99%
“…10,11 The main structures in the RAS spectra arise from transitions between surface states or surface modified bulk states. RAS is well suited for the analysis of metallic nanowires and has proved to be a useful tool in monitoring nanowire formation 12,13 or Peierls driven metal-insulator transitions in metallic nanowires.…”
Section: Introductionmentioning
confidence: 99%